Ação convulsivante do disseleneto de difenila em ratos: estudo dos mecanismos neuroquímicos e da toxicocinética - Prigol, Marina (2010)
In recent years have been identifical numerous pharmacological properties of a selenium compound, diphenyl diselenide [(PhSe)2]. Consequently, it is important the investigation of its toxic effect for a safe application in pharmacological studies. It is known that babies, in particular, have many physiological and biochemical changes related to development, which increase the susceptibility to toxic effects of drugs. Thus, the article 1 investigated the appearance of seizure episodes induced by (PhSe)2 when administered orally at doses of 5 to 500 mg/kg in rat pups (pos natal day 12-14) and the possible glutamatergic (article 2) and GABAergic (article 3) mechanisms involved in this process. Some studies using different experimental models have demonstrated the most different pharmacological and toxicodynamics properties of (PhSe)2. However, little is known about the toxicokinetic disposition of this compound. Therefore, the aim of article 4 was to determine and quantify the plasma levels of (PhSe)2 in adult mice and rats after oral (p.o.) administration of 500 mg/kg (PhSe)2; to verify the involvement of different routes of administration, vehicle and animal species in plasma levels of (PhSe)2 and in the onset of the first seizure episode induced by it. In article 5, it was determined and quantified the levels of (PhSe)2 in plasma, liver and brain of rat pups and these levels were correlated to the latency for the onset of the first seizure episode. To obtain more information about the compound, which were to supplement the data obtained, we carried out in vitro kinetic models. The manuscript 1 investigated the drug-like properties of (PhSe)2 in regards to stability, solubility, absorption and plasma protein binding (PPB) in vitro. In manuscript 2, it was conducted an in vitro study in order to identify possible metabolic pathways responsible for the biotransformation of (PhSe)2 in the body. Results of article 1 showed that administration of (PhSe)2 caused toxicity in rat pups, evidenced by the appearance of seizures. These were dose dependent and were, at least in part, related to oxidative stress. Among the mechanisms involved in the convulsive effect of (PhSe)2 were the interaction with: glutamatergic system by stimulating the inotropic glutamatergic receptors NMDA and by inhibiting the uptake of glutamate (Article 2); GABAergic system by antagonize the GABAA receptor, stimulating GABA transaminase enzyme and increasing GABA uptake (Article 3). The article 4 revealed that the maximum concentration of (PhSe)2 in the plasma of adult rats and mice occurred 30 minutes after p.o administration of the compound and remained detectable up to 8 hours after administration. The use of different routes of administration (intraperitoneal (i.p.), p.o., subcutaneous (s.c.)) or vehicle (canola oil or dimethyl sulfoxide (DMSO)) in rats and mice indicated that the onset of the first seizure episode and plasma levels are dependent on the route of administration (i.p. > p.o. > s.c.), vehicle (DMSO > canola oil) and animal species (mouse > rat). In article 5, it was observed that rat pups showed seizures even presenting lower plasma values of (PhSe)2 as compared to adults. This result demonstrated that rat pups are more sensitive to the toxic effects of (PhSe)2 than adult rats. Levels of (PhSe)2 in the liver and brain of rat pups showed a negative correlation with the latency to the first seizure episode. The manuscript 1 showed that (PhSe)2 has chemical and biological stability. However, the compound has a low solubility in water, a high partition coefficient octanol-water and an extensive plasma protein binding. Manuscript 2 indicated that (PhSe)2 is not biotranformed by Phase I reactions, catalyzed by cytochrome P450. It reacted chemically with reduced glutathione (GSH) and N-acetylcysteine (NAC) to form adducts or reacts with protein SH groups. The presence of GSH or NAC in the incubation medium decreased the binding of (PhSe)2 protein. Finally, it was observed that (PhSe)2 reduced the activity of cytochrome P450. Together, the data presented showed that the intensity of toxic effects caused by (PhSe)2 are directly related to its toxicokinetic.